A systematic procedure for synchronizing hyperchaos via observer design - GIUSEPPE GRASSI; Saverio Mascolo (Journal of Circuits, Systems and Computers, 2002)
In this Letter a systematic procedure for synchronizing different classes of hyperchaotic systems is illustrated. The approach can be applied to dynamic systems with one or more nonlinear elements as well as to time delay systems. The method is rigorous and systematic. Namely, if a structural property related to the drive system is satisfied, it is easy to design the synchronizing signal and the response system, which is chosen in the observer form. The technique is successfully applied to a recent example of 8th order circuit, to a cell equation in delayed Cellular Neural Networks and to an example of high dimensional system, which consists of five identical coupled Chua’s circuits forming a ring. Simulation results are reported to show the performances of the technique.